Poisoning density functional theory with benchmark sets of difficult systems. Issue 11 (4th March 2022) - Gould, Tim; Dale, Stephen G.
Abstract : "Poison sets" introduced in this work specifically target failures of density functional approximations. They thereby offer insights into hard computational chemistry problems via novel benchmarking strategies. Abstract : Large benchmark sets like GMTKN55 [Goerigk et al., Phys. Chem. Chem. Phys., 2017, 19, 32184] let us analyse the performance of density functional theory over a diverse range of systems and bonding types. However, assessing over a large and diverse set can miss cases where approaches fail badly, and can give a misleading sense of security. To this end we introduce a series of 'poison' benchmark sets, P30-5, P30-10 and P30-20, comprising systems with up to 5, 10 and 20 atoms, respectively. These sets represent the most difficult-to-model systems in GMTKN55. We expect them to be useful in developing new approximations, identifying weak points in existing ones, and to aid in selecting appropriate DFAs for computational studies involving difficult physics, e.g. catalysis.